OCTREOTIDE FOR TREATMENT RECURRENT HYPOGLYCEMIA INDUCED BY SULFONYLUREA: A CASE REPORT AND LITERATURE REVIEW - Yuddy Imowanto; Taufiq Abdullah; Tanjoyo, Hartadi (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
Overdose can cause hypoglycemia, which is unresponsive to dextrose treatment alone. Octreotide, though not universally used, is an antidote for sulfonylurea overdose. We present a case report of a 62-year-old male who mistakenly consumed six tablets of sulfonylurea (Glibenclamide®), thinking they were loperamide for diarrhea. He developed dizziness, diaphoresis, vomiting, and unconsciousness. Physical examination revealed a GCS of 225, blood pressure of 188/79 mmHg, heart rate of 85 bpm, respiratory rate of 24/min, and oxygen saturation of 99%. Blood results showed RBS at 13 mg/dl, normal CBC, unremarkable blood gas analysis, hypokalemia at 2.87 mmol/l, and normal RFT and LFT. The patient was treated with bolus Dextrose 40%, maintenance Dextrose 10%, and hydrocortisone 100 mg, but blood sugar remained refractory for 1 hour despite increasing glucose infusion. After 5 hours without satisfactory results, we administered the first dose of octreotide (50 IU IV), resulting in a hypoglycemic interval lasting 2.5 hours. After a second dose of 50 IU octreotide, hypoglycemia was resolved. The patient was moved to the general ward and survived. In this case, octreotide extended the interval of hypoglycemia and reduced the need for dextrose. Using octreotide for conditions other than sulfonylurea overdose is not recommended.